CASE STUDY OF A FRONTAL SYNDROME - Sánchez Rodríguez, Juan Luis; López Alburquerque, José Tomás; Sayago Arenas, Antonia María (Anales de Psicología / Annals of Psychology, 1999)
A wide range of behavioural and cognitive changes is 0bserved in the persons who have undergone frontal lesions. This symptomology can vary greatly depending above all on the location, extent, depth and laterality of the lesion. Affective, personality, motivation, attention, perception, memory, reasoning, problem-solving, language and motor control disorders have all been described. Our aim here is to comment on a case of frontal lesion caused by a traumatic brain injury, by describing in detail the nature of the patient’s deficiencies. A wide and important range of tests were used for the neuropsychological study of the patient, leading us to conclude, as we shall state in the Results section, that the subject suffers from a classic frontal syndrome.